Islamic Psychology and Its Clinical Impact: a Systematic Literature Review - Nurhidayat, Adhi Wibowo (Journal of Islamic Medicine, 2026)
Background: Islam and psychology are phrases aim to describe intellectual movements developed in psychology field, connecting Islam and psychology. Islamic Psychology itself refers to psychology that developed from Islamic sources, as an Islamic version of psychology.Objective: This paper aims to describe the implementation of Islamic psychology as a branch of modern psychology. This is a library study using Systematic Literature Review approach and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol. Methods: Using ProQuest dan Google Scholar search engine, 2,981 articles between 2013-2023 has been detected, and 6 papers has been chosen to be reviewed. These articles then analyzed using four research questions regarding methods, support and barrier factors in implementing Islamic psychology, and its impact for both patients and therapists. Results: At present, Islamic scholars support the development of Islamic psychology worldwide. Unfortunately, no agreement so far among researchers and clinicians regarding definition, theory, and its practice in this field. We do need the standard of Islamic psychology and psychotherapy that easily implemented in daily practice.  Keywords: psychology, Islam, Islamic psychology, psychotherapy, implementation